As concepções de alfabetização e letramento nos discursos e nas práticas de professoras alfabetizadoras: um estudo de caso em uma escola municipal de Belo Horizonte - Kely Cristina Nogueira Souto (2009)
This research consists of a case study developed by two teachers working with 6 years old students in municipal school classrooms in the city of Belo Horizonte. The general aim is to comprehend the theoretical and methodological assumptions that support the literacy practices, establishing relationships with the actions and the process of initial and continuous formation, and regarding the teachers roles. The following specific objectives are also highlighted: to analyse the teachers discourse about the process of learning to read and to write; to identify what they think about this process and what they do; to express the concept of learning to read and to write and the concept of literacy based on the teachers practices; to analyse the relationships between the theoretical conception and the practice present in the work developed by the teachers; to analyse the knowledge on the speeches and practices of the teachers that define the orientation of the work proposal; to describe the strategies arranged by the teachers and the nature of the pedagogical material used on the practices of reading and writing. The theoretical support sustained itself on the studies concerning the acquisition of the system of writing, psychogenesis of reading and writing, literacy, and the teachers academic background, especially the studies by Ferreiro, Teberosky, Soares, Bakhtin, Vygotsky, Tardif, Gauthier among others. The methodology consists of interviews with the teachers, observations and filming in classrooms, as well as the analysis of material collected in classrooms setting. The observation of the set of classes allowed the organization of analysis categories that represent the events of literacy proposed by the teachers. These categories concern the adaptation of the system of writing, reading, composition, and orality. The results of this study proved that the practice of writing language acquisition and the practice of literacy can occur in an integrated way or not and that the specific activities concerning the appropriation of the writing process, i.e., those that allow the analysis of the microstructure of the language, cannot always sustain itself on the texts available in classrooms. Distinct sources of knowledge converge into the construction of the concepts of writing and literacy by the teachers, but, on this research, the emphasis was placed on the professional experience, along with the workmates, more experienced teachers inside the school. The teachers speech also highlights that many of their pedagogical practices are directed by the intuition, which becomes constitutive from the practice of the profession work. The way in which they refer to the intuition makes it possible to recognize that this one represents their subjectivities or a way to legitimate the pedagogical doing itself.